Analisis Implementasi Kebijakan Sistem Informasi Manajemen Kepegawaian (SIMPEG) Pada Kantor Sekretariat Dpd Ri Provinsi Kepulauan Riau - Ai Nunung; Dian Candra Fatihah; Lalas Sulastri; Eka Mareta (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2026)
The Personnel Management Information System, known as SIMPEG, is an element of e-Government designed to oversee data, administration, and personnel management within local governments. When utilized effectively, SIMPEG can deliver precise and readily available information, as the data collection method is swift and accurate, provided there are no mistakes during entry. The purpose of this study is to evaluate the execution of the SIMPEG policy at the DPD RI Secretariat Office located in the Riau Islands Province. The findings of this research indicate that SIMPEG has been implemented fairly well, but a significant issue that must be addressed pertains to human resources. There is a need for dedicated IT personnel to oversee the performance of all software and hardware operations at the DPD RI Secretariat Office for the Riau Islands Province.